Impact of Human Activities on Biodiversity in Yola North Local Government Area, Adamawa State, Nigeria - F. M, AHMED; F. A., Sabiya; K. A, Abubakar; P., Vandi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Primary reasons for biodiversity loss are environmental pollution, destruction of natural habitats, overuse of biological resources, and population explosion. This study aimed to ascertain the impact of human activities on biodiversity in Yola North LGA. Descriptive survey research design was employed for the distribution of well-structured questionnaire. The sample for the study comprises 384 residents that was randomly selected from Doubeli, Jambutu, Karewa, Luggere, and Nasarawo Wards of Yola North LGA, Adamawa State. The data was analysed using Statistical Package for Social Sciences (SPSS) version 23.0. The analysis of the impact of population growth on biodiversity showed that majority of the respondents agreed that population affects; air, water and fishing activities, the impact of pollution on biodiversity is shown in the contamination of water bodies, reduced agricultural yield and tree growth. The responses of the respondents showed that majority agreed that habitat loss restrict animals from moving freely and can causes extinction in insect species. The study found that pollution significantly impacts biodiversity, aligning with global studies. Land use change was also found to significantly impact biodiversity, which is consistent with global research. Habitat loss was found to significantly impact biodiversity, which aligns with global studies.